The Contribution of Liver Sinusoidal Endothelial Cells to Clearance of Therapeutic Antibody - James, Bethany H.; Papakyriacou, Pantelitsa; Gardener, Matthew J.; Gliddon, Louise; Weston, Christopher J.; Lalor, Patricia F. (Frontiers in Physiology, 2022)
Many chronic inflammatory diseases are treated by administration of ‘biological’ therapies in terms of fully human and humanized monoclonal antibodies or Fc fusion proteins. These tools have widespread efficacy and are favoured because they generally exhibit high specificity for target with a low toxicity. However, the design of clinically applicable humanized antibodies is complicated by the need to circumvent normal antibody clearance mechanisms to maintain therapeutic dosing, whilst avoiding development of off target antibody dependent cellular toxicity. Classically, professional phagocytic immune cells are responsible for scavenging and clearance of antibody via interactions with the Fc portion. Immune cells such as macrophages, monocytes, and neutrophils express Fc receptor subsets, such as the FcγR that can then clear immune complexes. Another, the neonatal Fc receptor (FcRn) is key to clearance of IgG in vivo and serum half-life of antibody is explicitly linked to function of this receptor. The liver is a site of significant expression of FcRn and indeed several hepatic cell populations including Kupffer cells and liver sinusoidal endothelial cells (LSEC), play key roles in antibody clearance. This combined with the fact that the liver is a highly perfused organ with a relatively permissive microcirculation means that hepatic binding of antibody has a significant effect on pharmacokinetics of clearance. Liver disease can alter systemic distribution or pharmacokinetics of antibody-based therapies and impact on clinical effectiveness however few studies document the changes in key membrane receptors involved in antibody clearance across the spectrum of liver disease. Similarly, the individual contribution of LSEC scavenger receptors to antibody clearance in a healthy or chronically diseased organ is not well characterised. This is an important omission since pharmacokinetic studies of antibody distribution are often based on studies in healthy individuals and thus may not reflect the picture in an ageing or chronically diseased population. Therefore, in this review we consider the expression and function of key antibody-binding receptors on LSEC, and the features of therapeutic antibodies which may accentuate clearance by the liver. We then discuss the implications of this for the design and utility of monoclonal antibody-based therapies.